2015
DOI: 10.1159/000445907
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophy of the Great Toenail by Subungual Exostosis and Hyperostosis: Three Case Reports with Different Clinical Presentations

Abstract: Subungual exostoses and hyperostoses of the great toenail are a differential diagnosis of nail tumors. We present 3 cases of subungual exostosis/hyperostosis with secondary nail dystrophy: a 36- and a 37-year-old woman as well as an 8-year-old boy. Two of the 3 patients suffered from pain. The 2 female patients presented with the classic dorsolateral firm protrusion, while the child presented with bilateral nail dystrophy with lateral wall hypertrophy. In this later case, a bony ridge was identified, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(22 reference statements)
1
6
0
1
Order By: Relevance
“…In the work of Piccolo et al, 2 patients were under 10 years of age [4]. Other authors have reported sporadic cases [5,6]. In our context, half of the SUE cases noted in patients less than 16 years of age involved children less than 10 years of age.…”
Section: Discussionsupporting
confidence: 43%
“…In the work of Piccolo et al, 2 patients were under 10 years of age [4]. Other authors have reported sporadic cases [5,6]. In our context, half of the SUE cases noted in patients less than 16 years of age involved children less than 10 years of age.…”
Section: Discussionsupporting
confidence: 43%
“… 1 It occurs most commonly in children and young adults, with a female/male ratio of 2:1, and often affects the great toe. 2 , 3 Individuals at increased risk for subungual exostosis include those with trauma, chronic infection, tumor, hereditary anomalies, and the activation of a cartilaginous cyst, although its etiology and pathogenesis are not clearly established. 1 Its clinical manifestations are asymptomatic or painful subungual nodules.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Most commonly, subungual exostosis arises within the great toe of young individuals. 2 , 3 The nail plate is elevated due to a firm subungual nodule produced by an exostosis. Dermoscopic features of the affected nail include vascular ectasia, hyperkeratosis, onycholysis, and ulceration, with vascular ectasia being the most common finding.…”
Section: Introductionmentioning
confidence: 99%
“…Excision of the entire lesion, including the fibrocartilaginous cap, is crucial for prevention of local recurrence. 21 Postoperative recurrence of SE has been reported, followed by spontaneous regression. 22 Complete excision of the lesion and careful separation from underlying nail bed structures yield the lowest rates of recurrence and future complications.…”
Section: Discussionmentioning
confidence: 99%